An Introduction to the Passage of Energetic Particles through Matter - Carron, N.J (Taylor & Francis, 2006)
Identifying where to access data, extracting a needed subset from available resources, and knowing how to interpret the format in which data are presented can be time-consuming tasks for scientists and engineers. By collecting all of this information and providing a background in physics, An Introduction to the Passage of Energetic Particles thr